Pengaruh Partisipasi Anggaran, Sistem Keuangan Desa, Prinsip-Prinsip Good Governance dan Pemberdayaan masyarakat Terhadap Kualitas Anggaran Pendapatan dan Belanja Desa Kotawaringin Timur - Rosalia Sihotang; Sri Yuni; Ferry Christian (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
This study aims to determine the effect of the variable Budget Participation, Village Financial System, Good Governance Principles, and Community Empowerment on the Quality of Village Income and Expenditure Budget (Empirical Study of Village Apparatus, Kotabesi Subdistrict, Kotawaringin Timur Regency). This type of research used in this research is quantitative research. This study used a survey method with a questionnaire as the instrument. The population in this study were village officials in Kotabesi Subdistrict, Kotawaringin Timur Regency. The sample in this study as many as 75 respondents obtained by proportional sampling technique. The analysis technique used is multiple regression analysis. The results of this study conclude that in the partial test (t) the independent variable (1) Budget participation affects the quality of the Village Income and Expenditure Budget (2) The Village Financial System has no effect on the Quality of the Village Budget (3) The Principles of Good Governance have an effect the Quality of the Village Revenue and Expenditure Budget (4) Community Empowerment has no influence on the Quality of the Village Revenue and Expenditure Budget. The simultaneous test results show that Budget Participation, Village Financial Systems, Good Governance Principles, and Community Empowerment have a simultaneous effect on the quality of the Village Income and Expenditure Budget